Pengaruh takaran dan interval pemupukan urea tablet terhadap pertumbuhan dan hasil cabal di lahan pasir pantai bugel=The effect of dosage and fertilizing frequency of targeted urea on growth and yield of hot pepper ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
The aimed of this research was to know the effectiveness of dosage and fertilizing frequency of tablet urea on growth and yield of red pepper on beach sandy soil. Treatments used in this experiment were arranged in 3 x 2 factorials + 1 control in a Randomized Complete Block Design with three blocks as replications. The first factor was dosage of tablet urea with three levels, i.e. 179.2, 358.4, and 537.6 kg/ha, and the second factor was fertilizer application frequency with two levels, i.e. once time at a week after transplanting (wat) and three times at one, three, and, five wat. The control was fertilized with 358.4 kg/ha of granule urea directly at one wat. The result showed that tablet urea fertilizer could improved the plant dry weight 38.26, net assimilation rate 45, crop growth rate 51.69, yield per hectare 75.31, and harvest index 134.89 %. respectively. Interaction effect was found on the number of productive branch and net assimilation rate.